Optimization of inulin:Oligofructose proportion and non-thermal processing to enhance microbiological and sensory properties of fiber-enriched strawberry juice. (July 2017) - Cassani, L.; Tomadoni, B.; Moreira, M.R.; Ponce, A.; Agüero, M.V.
Abstract: Hurdle effect of vanillin concentration (0–1.25 mg/mL) and ultrasound time (0–30 min) with juice formulation (inulin:oligofructose proportion) on microbiological and sensory quality of strawberry juice after 14 days of storage at 5 °C were studied. Response surface methodology (RSM) and Box-Behnken design were used to find the conditions that simultaneously optimize: mesophilic aerobic bacteria, Enterobacteriaceae and total coliform and yeasts and molds (as microbiological indices) and overall visual quality (OVQ), typical strawberry odor and off-odor (as sensory attributes). Individual optimization of each response was carried out and compared with a simultaneous optimization using the Desirability function. Determination coefficients (R 2 ) for the second-order models adjusted by RSM were above 96%. Microbiological indices were significantly affected by vanillin whatever ultrasound time and fibers proportion were assayed. Vanillin and ultrasound resulted critical factors for all sensory attributes studied. Fibers proportion did not modify microbiological and sensory indices. Conditions that simultaneously optimize all responses were: 1.25 mg/mL of vanillin, 7.5 min of ultrasound time and 5:3 of inulin:oligofructose proportion. These results were validated and it was demonstrated that juice treated under optimal conditions resulted with enhanced microbial and sensory attributes. Highlights: Strawberry juice was enriched with fibers and preserved by ultrasound and vanillin. Microbiological and sensory indices were evaluated at 14 d of refrigerated storage. Quality indices were simultaneously optimized with Response Surface Methodology. An enriched and shelf-stable strawberry juice was obtained at optimal conditions.